2022
DOI: 10.1038/s41589-022-01177-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional E3 ligase hotspots and resistance mechanisms to small-molecule degraders

Abstract: Targeted protein degradation is a novel pharmacology established by drugs that recruit target proteins to E3 ubiquitin ligases. Based on the structure of the degrader and the target, different E3 interfaces are critically involved, thus forming defined "functional hotspots". Understanding disruptive mutations in functional hotspots informs on the architecture of the assembly, and highlights residues susceptible to acquire resistance phenotypes. Here, we employ haploid genetics to show that hotspot mutations cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Taken together, these results suggest that MZ1 resistance may arise from combinatorial effects of attenuated target degradation, lower production of IBM peptides, and dysfunctional cell death signaling. Previous reports indicate that the mechanisms of acquired 33,34 or engineered 35 resistance to targeted BRD4 degradation impact ligase machinery; our collective findings emphasize how these differences converge on the reduced capacity to produce IBM (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Lack Of Iap Modulation Underlies the Disconnect Between Mz1 ...mentioning
confidence: 64%
“…Taken together, these results suggest that MZ1 resistance may arise from combinatorial effects of attenuated target degradation, lower production of IBM peptides, and dysfunctional cell death signaling. Previous reports indicate that the mechanisms of acquired 33,34 or engineered 35 resistance to targeted BRD4 degradation impact ligase machinery; our collective findings emphasize how these differences converge on the reduced capacity to produce IBM (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Lack Of Iap Modulation Underlies the Disconnect Between Mz1 ...mentioning
confidence: 64%
“…This allows selection of therapeutically enticing CRL E3 ligases, taking into account their characteristics such as disease relevance, expression pattern, and target complementarity. In fact, recently, we have shown that essentiality of an E3 ligase can have a profound impact on the emergence of resistance to degrader modalities, further highlighting the need to expand the targetable E3 ligase space . In principle, ligase tracing assays capture POI recruitment on a proteome-wide scale.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recently, we have shown that essentiality of an E3 ligase can have a profound impact on the emergence of resistance to degrader modalities, further highlighting the need to expand the targetable E3 ligase space. 48 In principle, ligase tracing assays capture POI recruitment on a proteome-wide scale. Future research will be required to determine the threshold of neo-substrate abundance required for this assay.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…To this goal, base-editor screens, deep mutational scanning (DMS), and CRISPR tiling screens can play an important role. For instance, both DMS and CRISPR tiling have recently highlighted hotspots in ligase and POI that are functionally relevant for degrader activity. , …”
Section: Molecular Glue Degrader Discovery Via Advanced Phenotypic Sc...mentioning
confidence: 99%
“…For instance, both DMS and CRISPR tiling have recently highlighted hotspots in ligase and POI that are functionally relevant for degrader activity. 237,238…”
Section: Maximizing the Depth Of Downstream Analysismentioning
confidence: 99%